Evaluation of the cross-protective effect of VR2332 modified live virus vaccine against a recombinant NADC34-like porcine reproductive and respiratory syndrome virus - Wu, Yu; Lin, Limiao; Gao, Xiaopeng; Zheng, Jiaying; Yin, Lijuan; Zhao, Haishen; Ren, Bohua; Wang, Lianxiang; Li, Qunhui (Frontiers in Veterinary Science, 2024)
In recent years, NADC34-like strains of porcine reproductive and respiratory syndrome virus have gradually emerged as mainstream strains on Chinese pig farms. These strains have high mutation rates and can recombine with local strains, representing great challenges to prevention and control efforts. Previously, a new recombinant NADC34-like subtype strain was isolated in our laboratory. Herein, we evaluated the cross-protective effect of the VR2332 modified live virus (MLV) against the novel NADC34-like recombinant strain using the immune challenge protection test in piglets and sows. The results revealed that immunization with the vaccine in piglets significantly reduced viremia, lung damage and stimulated the production of PRRSV-N antibodies. In the sow challenge experiment, one abortion and one death were recorded in the positive control group, and the survival rate of offspring was only 25%. However, there were no sow deaths or abortions in the immunization group during the experiment, and the average piglet survival rate was high at 76.5%. In general, the VR2332 MLV confers a certain extent of cross-protection against the NADC34-like recombinant strain, providing an effective reference and guidance for prevention and control efforts and clinical vaccine use.